KETERKAITAN MELEMAHNYA RUPIAH TERHADAP KONFLIK GEOPOLITIK: STUDI DAMPAK DI WILAYAH TIMUR TENGAH - Ainnaya Ardyanti Putri; Fayza Safana Fitria; Rindi Cahya Mustika Ayu; Arman Hadid; Muhammad Naufal Arzaq; Suryo Ediyono (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
The rupiah's exchange rate against the U.S. dollar has experienced significant fluctuations driven by various global economic and political factors. One of the key contributing factors is geopolitical conflict in the Middle East, which has caused widespread global economic instability and disproportionately affected developing countries, including Indonesia. This study analyzes the relationship between the weakening of the rupiah and Middle East geopolitical conflicts. It further examines their broader impact on Indonesia's economic conditions, based on a qualitative literature review of journals, scientific articles, and news sources from 2021 to 2026, a period marked by significant escalation of Middle East conflicts. The results indicate that this relationship occurs through three main transmission channels. Through the energy channel, conflicts disrupted global oil supplies, particularly through threats to close the Strait of Hormuz, leading to rising crude oil prices and increasing Indonesia's energy import burden. Through the capital flow channel, heightened geopolitical risk prompted global investors to shift their assets toward safer instruments such as the U.S. dollar and gold, thereby pressuring the rupiah's exchange rate. Through the international trade channel, geopolitical tensions disrupted global supply chains, particularly in the energy and strategic industrial sectors, further intensifying domestic economic pressure. This phenomenon was evident in the sharp decline of the Jakarta Composite Index and the rupiah's depreciation to a new psychological threshold amid Iran-Israel tensions, followed by its recovery after the United States-Iran peace agreement. The study concludes that rupiah stability is determined not only by domestic factors but is also significantly influenced by global geopolitical dynamics, necessitating adaptive economic resilience and diplomatic strategies.